Ungrading : why rating students undermines learning (and what to do instead) - Blum, Susan Debra; Kohn, Alfie (Morgantown West Virginia University press, 2020)
"The moment is right for critical reflection on what has been assumed to be a core part of schooling. In Ungrading, fifteen educators write about their diverse experiences going gradeless. Some contributors are new to the practice and some have been engaging in it for decades. Some are in humanities and social sciences, some in STEM fields. Some are in higher education, but some are the K-12 pioneers who led the way. Based on rigorous and replicated research, this is the first book to show why and how faculty who wish to focus on learning, rather than sorting or judging, might proceed. It includes honest reflection on what makes ungrading challenging, and testimonials about what makes it transformative"--
Introduction: Why ungrade? Why grade? / Susan D. Blum -- How to ungrade / Jesse Stommel -- What going gradeless taught me about doing the "actual work" / Aaron Blackwelder -- Just one change (just kidding) : ungrading and its necessary accompaniments / Susan D. Blum -- Shifting the grading mindset / Starr Sackstein -- Grades stifle student learning. Can we learn to teach without grades? / Arthur Chiaravalli -- Let's talk about grading / Laura Gibbs -- Contract grading and peer review / Christina Katopodis and Cathy N. Davidson -- Critique-driven learning and assessment / Christopher Riesbeck -- A STEM ungrading case study : a reflection on first-time implementation in organic chemistry II / Clarissa Sorensen-Unruh -- The point-less classroom : a math teacher's ironic choice in not calculating grades / Gary Chu -- Grade anarchy in the philosophy classroom / Marcus Schultz-Bergin -- Conference musings and the G-word / Joy Kirr -- Wile E. Coyote, the hero of ungrading / John Warner -- Conclusion: Not simple but essential / Susan D. Blum.
Includes bibliographical references and index.
Keywords: Grading and marking (Students) -- United States; Students -- Rating of -- United States